Wspieranie zmian kultury organizacyjnej poprzez programy etyczne przedsiębiorstw - Stankiewicz, Janina; Łychmus, Patrycja (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Changing of an organizational culture is a difficult and long-lasting process. Therefore, there is a necessity for searching such means or instruments of changes which would facilitate that process and make the transformations permanent. One of the possibilities is supporting the changes process through intentional created or modified ethical programme of enterprise. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 406-412